Sistem Kadasan Pada Usaha Penggemukkan Sapi Ditinjau Dari Perspektif Ekonomi Islam - Satria Darmansyah; Busaini Busaini; Ihsan Rois (Universitas Islam Negeri Sumatera Utara, 2023)
The purpose of this study was to find out and analyze the application of the kadasan system to the fattening of beef cattle from an Islamic economic perspective in West Lombok district. This research includes qualitative research with explanative methods. There are three types of informants used in this study, namely main informants, key informants and additional informants. Determination of informants using purposive and snowball techniques and the researcher acts as a key instrument from the beginning to the end. Data collection techniques use observation, in-depth interviews and triangulation so that the information obtained is more tested for its validity. Based on the results of the research that has been carried out, several conclusions can be drawn as follows: 1) Application of the Kadasan System to fattening cattle in the district in terms of West Lombok, all pillars and conditions have been implemented which include the first: al-qidayn (two people who make an agreement ), second: mal (shares or capital), third: charity (managed business), fourth: al-ribhu (profit or profit) and fifth: sighat (statement of consent and acceptance from both parties). 2) The application of the kadasan system to fattening cattle in West Lombok district uses a Mudharbah Muqayyadah Contract in accordance with an Islamic economic perspective.